Apelin as a CNS-specific pathway for fenestrated capillary formation in the choroid plexus - Lukas Herdt; Stefan Baumeister; Jeshma Ravindra; Jean Eberlein; Christian S. M. Helker (Nature Communications)
Abstract The cerebral vasculature consists of a heterogenous network of blood vessels, including barrier-forming capillaries with blood-brain-barrier (BBB) properties and fenestrated capillaries specialized for molecular exchange. While key pathways regulating BBB vessel formation have been identified, the mechanisms driving fenestrated vessel development remain poorly understood. Here, we identify Apelin signaling as a critical, cell type-specific pathway required for the formation of fenestrated capillaries in the choroid plexus (CP), while being dispensable for angiogenesis and barriergenesis of adjacent BBB vessels. Notably, apelin receptor b (aplnrb) expression closely mirrors that of the canonical fenestrated endothelium marker, plasmalemma vesicle-associated protein b (plvapb), highlighting aplnrb as a second marker for the fenestrated endothelium. However, our data indicate that Apelin signaling does not regulate expression of plvapb. Furthermore, we identify a population of undifferentiated pre-programmed leptomeningeal fibroblast as the Apelin source, regulating fenestrated vessel formation in the CP. Utilizing our previously engineered APLNR-cpGFP conformational biosensor we map localized Apelin ligand hotspots across the brain, which guide the development of fenestrated blood vessels in the CP. Collectively, our findings uncover a meningeal-vascular signaling axis that promotes fenestrated vessel formation in the CP and is essential for establishing cerebrovascular heterogeneity.